2004
DOI: 10.1097/01.fpc.0000114750.08559.32
|View full text |Cite
|
Sign up to set email alerts
|

High plasma pravastatin concentrations are associated with single nucleotide polymorphisms and haplotypes of organic anion transporting polypeptide-C (OATP-C, SLCO1B1)

Abstract: This study aimed to characterize possible relationships between polymorphisms in the drug transporter genes organic anion transporting polypeptide-C (OATP-C, SLCO1B1), OATP-B (SLCO2B1), multidrug resistance-associated protein 2 (MRP2, ABCC2) and multidrug resistance transporter (MDR1, ABCB1) and the pharmacokinetics of pravastatin. We studied 41 healthy Caucasian volunteers who had previously participated in pharmacokinetic studies with pravastatin. Six volunteers had a very high pravastatin AUC value and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
322
9
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(368 citation statements)
references
References 47 publications
34
322
9
3
Order By: Relevance
“…For urinary data, the mean Ae 0-24 and CLr 0-24 values of both pravastatin and RMS-416 were not markedly different between these groups (data not shown). It was somewhat unexpected that there were no significant differences in any pharmacokinetic parameters of pravastatin among SLCO1B1 genotypes, because previous studies provided accordant evidence that SLCO1B1*15 is associated with remarkably elevated plasma levels of pravastatin (Niemi et al 2004;Nishizato et al 2003). Because of the instability in acid conditions, pravastatin underwent acid-catalyzed conversion to form RMS-416 (3 0 a-isopravastatin) in the stomach after oral administration, and a considerable amount of RMS-416 was detectable in plasma, urine, and feces (Everett et al 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For urinary data, the mean Ae 0-24 and CLr 0-24 values of both pravastatin and RMS-416 were not markedly different between these groups (data not shown). It was somewhat unexpected that there were no significant differences in any pharmacokinetic parameters of pravastatin among SLCO1B1 genotypes, because previous studies provided accordant evidence that SLCO1B1*15 is associated with remarkably elevated plasma levels of pravastatin (Niemi et al 2004;Nishizato et al 2003). Because of the instability in acid conditions, pravastatin underwent acid-catalyzed conversion to form RMS-416 (3 0 a-isopravastatin) in the stomach after oral administration, and a considerable amount of RMS-416 was detectable in plasma, urine, and feces (Everett et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Several single-nucleotide polymorphisms (SNPs) have been identified in SLCO1B1 (Nozawa et al 2002;Tirona et al 2001), and some are reported to be associated with alterations in the pharmacokinetics of certain substrate drugs, including repaglinide (Niemi et al 2005a), fexofenadine (Niemi et al 2005b), pitavastatin (Chung et al 2005;Ieiri et al 2007), and pravastatin (Mwinyi et al 2004;Niemi et al 2004;Nishizato et al 2003). Particularly subjects having SLCO1B1*15 allele (possessing both 388A [G and 521T[C) showed elevated systemic exposure of pravastatin as compared to subjects without this allele (Niemi et al 2004;Nishizato et al 2003). In contrast, some reports indicated that SLCO1B1*1b allele (possessing 388A [G) showed enhanced transport activity of OATP1B1 as compared with wild-type allele (i.e., *1a allele) (Maeda et al 2006;Mwinyi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The T521C SNP has been consistently linked with reduced transport activity of OATP1B1, both in vitro 54,[56][57][58] and in vivo. 53,59,60 The collective evidence indicates that statin blood concentrations are higher in subjects with the 521C allele, and a recent genome-wide study elucidated that the 521C allele is associated with an increased risk of simvastatin-induced myopathy. 61 Two haplotypes with nonsynonymous variations, *1b harboring A388G and *15 harboring A388G and T521C, have been frequently reported in Japanese, and the pravastatin blood concentration was significantly lower in *1b/*1b subjects than in *1a/*1a subjects.…”
Section: Organic Anion Transporting Polypeptide (Oatp)mentioning
confidence: 99%
“…[53][54][55] Among more than 40 mutations identified in SLCO1B, A388G (Asn130Asp) and T521C (Val174Ala) occur frequently and have been extensively investigated. The T521C SNP has been consistently linked with reduced transport activity of OATP1B1, both in vitro 54,[56][57][58] and in vivo.…”
Section: Organic Anion Transporting Polypeptide (Oatp)mentioning
confidence: 99%
“…Compared with wild-type OATP1B1, c.521T>C was associated with increased systemic exposure to multiple drugs, including oral pravastatin [23,24] , fexofenadine [25] , and lopinavir [26,27] . In addition, the co-administration of OATP1B1 inhibitors may affect the pharmacokinetics of its substrates.…”
mentioning
confidence: 99%